Who's up to the challenge? 37

Calculus Level 5

lim a 1 k = 1 n = 1 ( 1 ) k + n H k H n k + n a k + n = ζ ( a ) b ( ln d ) c f + ( ln h ) g i + j ln k l \lim _{a\rightarrow1^-}{\large \displaystyle\sum _{ k=1 }^{ \infty }{ \sum _{ n=1 }^{ \infty }{ { (-1) }^{ k+n }\dfrac { { H }_{ k }{ H }_{ n } }{ k+n }a^{k+n} } } }=\dfrac { \zeta (a) }{ b } -\dfrac { (\ln d)^c }{ f } +\dfrac { (\ln h)^g }{ i } +j\ln { k } -l

The equation above holds true, where H n H_n denotes the n th n^{\text{th}} harmonic number and a , b , c , , k , l a,b,c,\ldots,k,l are positive integers.

Find a + b + c + d + f + g + h + i + j + k + l 1 a+b+c+d+f+g+h+i+j+k+l-1 .

Notation : ζ ( ) \zeta(\cdot) denotes the Riemann zeta function .


The answer is 24.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Apr 15, 2016

Using the generating function of the Harmonic numbers n = 1 H n x n = ln ( 1 x ) 1 x x < 1 , \sum_{n=1}^\infty H_n x^n \; = \; - \frac{\ln (1-x)}{1-x} \qquad \qquad |x| < 1\;, we can write k = 1 n = 1 ( 1 ) k + n H k H n k + n a k + n = 0 a ln 2 ( 1 + x ) ( 1 + x ) 2 x d x \sum_{k=1}^\infty \sum_{n=1}^\infty (-1)^{k+n} \frac{H_k H_n}{k+n}a^{k+n} \; = \; \int_0^a \frac{\ln^2(1+x)}{(1+x)^2x}\,dx for any 0 < a < 1 0 < a < 1 , and hence that lim a 1 k = 1 n = 1 ( 1 ) k + n H k H n k + n a k + n = 0 1 ln 2 ( 1 + x ) ( 1 + x ) 2 x d x = 0 1 ln 2 ( 1 + x ) ( 1 x 1 x + 1 1 ( x + 1 ) 2 ) d x = 1 2 ln 2 x ( 1 x 1 1 x 1 x 2 ) d x = n = 3 1 2 x n ln 2 x d x \begin{array}{rcl} \displaystyle \lim_{a \to 1-}\sum_{k=1}^\infty \sum_{n=1}^\infty (-1)^{k+n} \frac{H_k H_n}{k+n}a^{k+n} & = & \displaystyle \int_0^1 \frac{\ln^2(1+x)}{(1+x)^2x}\,dx \\ & = & \displaystyle \int_0^1 \ln^2(1+x)\left( \frac{1}{x} - \frac{1}{x+1} - \frac{1}{(x+1)^2}\right)\,dx \\ & = & \displaystyle \int_1^2 \ln^2x\left(\frac{1}{x-1} - \frac{1}{x} - \frac{1}{x^2}\right)\,dx \\ & = & \displaystyle \sum_{n=3}^\infty \int_1^2 x^{-n} \ln^2 x\,dx \end{array} A couple of rounds of integration by parts gives 1 2 x n ln 2 x d x = 2 2 2 n ( n 1 ) ( ln 2 ) 2 2 n ( n 1 ) 2 ( ln 2 ) 2 2 1 n ( n 1 ) 3 \int_1^2 x^{-n} \ln^2x\,dx \; = \; \frac{2 - 2^{2-n} - (n-1)(\ln 2)2^{2-n} - (n-1)^2(\ln2)^22^{1-n}}{(n-1)^3} for all n 3 n \ge 3 , and hence lim a 1 k = 1 n = 1 ( 1 ) k + n H k H n k + n a k + n = 1 4 ζ ( 3 ) 1 3 ( ln 2 ) 3 + 1 2 ( ln 2 ) 2 + ln 2 1 \lim_{a \to 1-}\sum_{k=1}^\infty \sum_{n=1}^\infty (-1)^{k+n} \frac{H_k H_n}{k+n}a^{k+n} \; = \; \tfrac14\zeta(3) - \tfrac13(\ln2)^3 + \tfrac12(\ln2)^2 + \ln2 - 1 leading to the answer 3 + 4 + 3 + 2 + 3 + 2 + 2 + 2 + 1 + 2 + 1 1 = 24 3 + 4 + 3 + 2 + 3 + 2 + 2 + 2 + 1 + 2 + 1 - 1 \,=\,\boxed{24} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...